배전계통에 초전도한류기 적용시 OCR 및 Recloser 동작특성 분석 - 문종필(Jong-Fil Moon) (전기학회 논문지 P권, 61(4), 2012)
In this paper, the method of protective coordination is studied to install Superconducting Fault Current Limiter (SFCL) to power distribution system. If SFCL is installed, the protective coordination is not operated well because of the decreased fault current. Thus, the resetting method of protective devices is presented to coordinate protection system in power distribution system with resistor-type SFCL. The presented methods are divided into three parts; OCR, OCR-Recloser, OCR-Recloser-Recloser. The presented methods are proved through case studies using PSCAD/EMTDC simulation.